ANALISA PENGELOLAAN PERMINTAAN DAN KAPASITAS PRODUKSI UMKM JASA SULTAN EXPRESS - Windy Octaviana Manurung; Dewi Ratnasari; Tiara Annisah; Priscillia Paramitha Tanujaya (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2022)
MSME (Micro, Small and Medium Enterprises) is a term for business activities run by business entities, households and individuals which refers to productive economic enterprises. The classification is based on turnover and the amount of wealth and employees owned. MSMEs have a very big contribution in raising the wheels of the Indonesian economy, this is because the type of business has a role in expanding employment opportunities. Sultan Express Couriers are SMEs that have great potential to develop the shipping service industry. The purpose of this research is to find out how Sultan Express handles the increasing demand in a season in order to remain effective and timely as well as the branding of Sultan Express. The results show that Sultan Express can handle increasing demand in one season while still using low prices in order to attract consumers to use the services of MSMEs, Sultan Express services in handling demand if it goes up or down and the branding of Sultan Express is still offering the cheapest postage prices. in the city of Batam, namely at a cost of Rp. 6,000 throughout the city of Batam.